A Study of the Evolution of Secure Software Development Architectures (Journal of The Colloquium for Information Systems Security Education, 2018)
Emerging technologies such as containers, microservices, DevOps, Agile software development life cycle (SDLC), and cloud-native applications have gained popularity and traction in the industry and among enterprises. These modern application technologies and architectures are being adopted because they enable greater flexibility, scalability, portability and more rapid development. Consequently, how to build and maintain secure applications and systems is being reevaluated. Since the total responsibility is now larger and more complex, the application developer role is expanding to include greater security obligations and concerns. This paper explores the evolution of software development architectures and consequent implications on security, to better understand the technology landscape driving this change and its impacts on application development. To remain competitive, organization must be prepared to invest in ongoing training of their developers in the latest best practices. To remain relevant, higher education must adapt curriculums to prepare future professionals in the appropriate cybersecurity and secure coding practices to match the development shifts observed in industry.
Keywords: Secure Software Development; Agile SDLC; Container; Microservice; DevOps